Environmental, social and governance (ESG) reporting practices in Bangladesh : a critical examination of selected RMG firms - Zaman, Zona; Levermore, Roger; Zimmermann, Willi; Junaid, Muhammad; His Majesty the King's Scholarships (Pathum Thani : Asian Institute of Technology, 2024)
The main purpose of this study is to examine the current Environmental, Social and Governance (ESG) reporting practices of Ready-made Garments (RMG) firms in Bangladesh. The RMG industry, an integral part of Bangladesh's economy, is characterized by its rapid growth and complex challenges related to ESG reporting. The study reveals that, despite having the highest number of LEED (Leadership in Energy and Environmental Design) certified {u2018}green factories{u2019} in the world and BGMEA{u2019}s pledge to sustainability, the RMG sector in Bangladesh continues to struggle with ESG/CSR/sustainability reporting disclosure and transparency. This qualitative study, conducted over six months, utilizes purposive sampling from 18 diverse stakeholders, including firm executives, ESG experts, and investors. The research aims to assess the current level of ESG reporting in Bangladesh and explore the decision-making drivers influencing ESG practices in selected RMG firms listed under BGMEA. The study utilizes semi-structured interviews to gain in-depth insights. The methodological framework is underpinned by thematic analysis, employing Quirkos software to systematically identify and interpret patterns and themes emerging from the qualitative data. The findings of this study underscore the diverse approaches to ESG reporting among RMG firms in Bangladesh. The research highlights a proactive engagement by some firms with established frameworks like Global Reporting Initiative (GRI) standards, driven by strategic aims to penetrate European markets where ESG compliance is crucial. Yet, it also exposes widespread challenges including financial constraints, regulatory gaps, and the hurdles of implementing ESG practices comprehensively. These findings not only affirm the strategic value of ESG reporting for competitive advantage but also pinpoint the significant operational and regulatory discrepancies that deter full adoption and alignment with global benchmarks. The study contributes significantly to the scarce literature on ESG reporting in emerging economies, especially in a sector as pivotal as the RMG industry of Bangladesh, advocating for more rigorous, standardized, and transparent reporting mechanisms. Furthermore, the finding of this study has significant implications for international partners, policymakers, and industry stakeholders, advocating the need for more rigorous, standardized, and transparent ESG reporting practices to ensure sustainable and ethical operations.
A research submitted in partial fulfillment of the requirements for the degree of Master of Business Administration
Research Studies Project Report (M. BA.) - Asian Institute of Technology, 2024
Keywords: Clothing trade -- Bangladesh -- Case studies; Clothing factories -- Bangladesh -- Case studies; Social responsibility of business -- Bangladesh -- Case studies